Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Belanja Daerah Kabupaten Tapin Tahun 2007-2019 - Hariyadi, Muhammad David; Pahlevi, Khairi (PPJP ULM, 2023)
This research is a type of quantitative research that aims to determine the effect of Local Government Revenue and Balancing Fund on Regional Expenditure, and look for which variable is the most dominant. This research uses time series secondary data 2007-2019 from Local Government Finance Office: The Financial Management Section of Each Local Government in Tapin Regency. Data analysis technique in this research uses Multiple Linear Regression Analysis and Hypothesis testing uses coefficient of determination, F-statistic test, and t-statistic test with 5% significance level (0,05). The results of the tests indicate that the variable of Revenue Sharing Fund is the only independent variable that has a significant effect as well as being the most dominant variable to the Regional Expenditure. While the variable of Local Government Revenue, General Allocation Fund, and Special Allocation Fund have an insignificant effect on Regional Expenditure in Tapin Regency.